The ‘irrational’ taboos and ‘irrelevant’ traditions related to postpartum women’s health and well-being - Wong, Chin Mun; Faiz Daud,; Lavanyah A/P Sivaratnam,; Diana Safraa Selimin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Taboos and traditions refer to myths and non-scientific practices held by people across the world. A variety of taboos are practiced worldwide (including those relating to food, religious, and sexual beliefs), including in Malaysia. Most of the taboos that concern the postpartum period are related to postpartum physiological, emotional, and family dynamic changes. The aim of this systematic review is to explore the traditions and taboos practised among postpartum mothers in Malaysia, and to consider the purpose and health impact of their practice. A systematic search of journals in Malaysia was conducted using eight major databases: Scopus, Ovid Medline, Science Direct, SAGE, PubMed, Wiley Online Library, Google Scholar, and EBSCOhost. Articles from all journals published between 2013 and 2018 were assessed through the PRISMA checklist. From 17,945 papers screened, seven papers were selected for critical analysis using the Mixed Methods Appraisal Tool (2018). It was found that in Malaysia, certain postpartum traditions, including food taboos and behavioural and physical restrictions were conducted with the aim of maintaining the well-being of mother and baby, and to improve the healing process. Some of the practices were found to be irrelevant, whilst others had beneficial health impacts. Based on this review, the practice of certain taboos and traditions during the postpartum period was found to have both advantages and disadvantages. A rational approach is needed to weigh the practice against maternal safety and health. Thus, healthcare personnel should be sensitive to the role of taboos and traditions in the postpartum care of patients. The practice of traditions and taboos should be monitored for safe practice, along with a need for community-based education to avoid any unwanted issues as a result of its practice.